School of Dental Medicine 150th Anniversary Gala (Tufts Archival Research Center, 2019)
Video of the School of Dental Medicine's 150th Anniversary Gala on September 28, 2018 at the Museum of Science in Boston, MA. Program speakers included Richard Valachovic, President and CEO of ADEA; Dean Huw Thomas; President Anthony Monaco; and Swaitha Maripuri, D19.